Особливості роботи програмної системи для контролю спеціальних умов транспортування трансплантантів - Атакулова, К. Ю. (ХНУРЕ, 2021)
Software System for Control Special Conditions of Transplant Transplantation the relevance of which is unconditional, was developed with the aim of improving the statistics of successful transplants with the help of highquality monitoring of the state of the organ upon delivery.
Науковий керівник – Доцент кафедри ПІ Лещинський В.О.
Keywords: програмна система; транспортування трансплантантів